FLOW INJECTION- SPECTROPHOTOMETRIC DETERMINATION OF AMOXICILLIN BASED ON ITS OXIDATIVE CONDENSATION WITH 4-AMINOANTIPYRINE - Al-Abachi, Mouayed (Iraqi Journal of Science, 2024)
Simple methods were proposed for the spectrophotometric determination of amoxicillin (AMX) in pharmaceutical formulations . The methods are based on the reaction of AMX with 4-aminoantipyrine (4AAP)) in the presence of potassium persulphate in alkaline medium .The reaction water soluble red colour product is measured at λmax 510 nm using both batch and flow injection analysis (FIA) approach .The effect of chemical and physical parameters were investigated by univariate method. Under the optimum conditions ,calibration graphs were observed linear from 1-60 and 1-120 μg mL-1 AMX with detection limits of 0.173 and 0.395 μg mL-1 AMX by batch and FIA procedure respectively. The relative standard deviations of the proposed methods were less than 0.67 and 0.59 by batch and FIA procedure respectively. The FIA sample throughput was 40 h-1. The proposed methods were successfully applied to the determination of AMX in injections and capsules